Simply sustainable : moving toward plastic-free, low-waste living - Cameron, Lily, 1986- (Ten Speed Press, 2020)
"Transitioning to a zero-waste lifestyle means eliminating unnecessary clutter from your home and reducing your dependence on disposable goods, but it also comes with practical challenges that can seem daunting. In Simply Sustainable, perfection is not required. Whether you are looking for easy changes to get you started, or more advanced, high-impact tips for your low-waste home, these simple, effective steps will forever change your relationship to disposable plastic products. Lily Cameron shows readers how to gradually transition away from plastic and curate a minimal, beautiful home in the process"--